2020
DOI: 10.1111/1346-8138.15552
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab promotes engagement of cholecystokinin and its receptor in epidermal keratinocytes of psoriasis patients

Abstract: Psoriasis is mediated by immune cells and epidermal keratinocytes. Interleukin (IL)-17A is one of the most critical cytokines involved in the pathogenesis of psoriasis, as it stimulates keratinocytes to produce various cytokines and chemokines that recruit inflammatory cells to the skin. 1 Therefore, neutralizing biologics against IL-17A, as exemplified by secuk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The specificity of the antibodies was also confirmed by staining normal human skin cells with anti-CCKAR, anti-CCK, or rabbit IgG isotype control antibodies ( Figure 2 ). Similar to our previous studies ( Funakoshi et al., 2020 , 2019 ), epidermal KCs were positively stained with anti-CCKAR and anti-CCK antibodies but not with rabbit IgG isotype control antibody.
Figure 1 CCKAR is expressed in melanoma cells.
…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The specificity of the antibodies was also confirmed by staining normal human skin cells with anti-CCKAR, anti-CCK, or rabbit IgG isotype control antibodies ( Figure 2 ). Similar to our previous studies ( Funakoshi et al., 2020 , 2019 ), epidermal KCs were positively stained with anti-CCKAR and anti-CCK antibodies but not with rabbit IgG isotype control antibody.
Figure 1 CCKAR is expressed in melanoma cells.
…”
Section: Resultssupporting
confidence: 90%
“…Next, we evaluated the expression levels of CCK and its receptors in several skin tumor cell lines. We used normal human epidermal keratinocytes (NHEK) and Jurkat cells as positive controls for CCKAR and CCKBR, respectively (Funakoshi et al, 2020, Funakoshi et al, 2019, Lignon et al, 1991. Flow cytometric analysis revealed that B16-F1 mouse melanoma and A375 human melanoma cells expressed CCKAR, while CCKBR was hardly detected in these cells (Figure 3a).…”
Section: Cckar Is Expressed In Human Melanoma Cells and Melanoma And ...mentioning
confidence: 99%
See 1 more Smart Citation